Development of Learning Content Curation System Model on Online Courses at Syarif Hidayatullah UIN Jakarta - Indra Munawar; Yudhi Munadi; Ahmad Suryadi; Widia Winata (Syntax Corporation, 2022)
Content curation is not just sorting or selecting teaching materials. The main challenge lies in how to determine the most appropriate learning content with learning outcomes. Therefore, to answer the problems above, learning designers need a learning content curation system model as a guide or reference. This study aims to develop a model of a learning content curation system that is devoted to being a guide in sorting and selecting teaching materials. The research questions in this development research are: 1) is the model developed in accordance with the conceptual framework? 2) Is the developed model feasible and can be implemented? Therefore, this research uses formative research methods. As a consequence, a series of formative evaluation techniques were used to collect the necessary descriptive and formative data. The formative evaluation includes expert test, one-on-one evaluation, and field test. This study was attended by 4 (seven) experts (experts in learning design and e-learning), and 25 lecturers as research subjects. After going through three stages of formative evaluation, namely the creation of a tentative model, the feasibility of the model and the effectiveness of the model, this model is declared in accordance with the conceptual framework for curating learning content, feasible and can be implemented. So that it can be used as a model in curating learning content for certain courses in online learning. Keywords: instructional model; content curation; online learning, learning content curation system model